1998
DOI: 10.1084/jem.188.6.1091
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Hemoglobin Protease Secreted by the Pathogenic Escherichia coli Strain EB1

Abstract: Many pathogenic bacteria can use heme compounds as a source of iron. Pathogenic Escherichia coli strains are capable of using hemoglobin as an iron source. However, the mechanism of heme acquisition from hemoglobin is not understood for this microorganism. We present the first molecular characterization of a hemoglobin protease (Hbp) from a human pathogenic E. coli strain. The enzyme also appeared to be a heme-binding protein. Affinity purification of this bifunctional protein enabled us to identify the extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(179 citation statements)
references
References 48 publications
8
166
1
4
Order By: Relevance
“…Multiple iron-uptake systems, such as enterobactin, aerobactin and salmochelin, and the fungal siderophores ferrichrome and coprogen, have indeed been found in other E. coli strains (Otto et al, 1998). Besides these systems, yet another system encoding yersiniabactin (Ybt) siderophore synthesis and uptake appears to be present in the A0 34/86 strain, as detected here by the sequences of several irp and ybt genes.…”
Section: Resultsmentioning
confidence: 73%
“…Multiple iron-uptake systems, such as enterobactin, aerobactin and salmochelin, and the fungal siderophores ferrichrome and coprogen, have indeed been found in other E. coli strains (Otto et al, 1998). Besides these systems, yet another system encoding yersiniabactin (Ybt) siderophore synthesis and uptake appears to be present in the A0 34/86 strain, as detected here by the sequences of several irp and ybt genes.…”
Section: Resultsmentioning
confidence: 73%
“…It has recently been shown that pathogenic Escherichia coli strain EB1 can secrete a serine proteinase that is able to bind Hb, degrade it, and capture the released heme (35). So far, no regulatory role has been proposed for heme in this case.…”
Section: Discussionmentioning
confidence: 99%
“…5 Two well-studied examples are hemoglobin protease (Hbp), a serine protease involved in iron scavenging for the human pathogen E. coli EB1, 13 and plasmid-encoded toxin (Pet) from E. coli 042, a pathogenic strain that causes diarrhea. 14 The crystal structure of the Pet passenger domain has not been solved, but Pet and Hbp passenger domains share 26% sequence identity plus 43% sequence similarity.…”
Section: Introductionmentioning
confidence: 99%